Optimizing surgical outcomes in recurrent plunging ranula: a case report - Latheef, Nashwa A.; Sukumarapillai, Vishnu S.; Ayallil, Muhamed S. (International Surgery Journal, 2024)
A plunging ranula is the extravasation of saliva from the sublingual gland due to trauma or ductal obstruction. The saliva tracks through fascial planes into the submandibular space. While typically originating from the sublingual gland, it rarely involves the submandibular gland. Two types are recognized: simple oral ranula and plunging ranula. Various treatment approaches exist, particularly for preventing recurrence in the plunging type. This case report presents the clinical and radiological findings along with our surgical management of a recurrent plunging ranula using a combined intraoral and extraoral approach with dual salivary gland excision utilising intraoperative ultrasonography to ensure complete excision and prevent recurrence. We present the case of a 16-year-old female with recurrent plunging ranula following incomplete excision of a sublingual ranula in the past. Initially asymptomatic after the first surgery, the patient later developed swelling in the mouth floor and neck. The recurrence was managed using a combined intraoral and extraoral approach for complete excision of the sublingual and submandibular glands, along with the cervical extension of the ranula, guided by intraoperative ultrasonography. Postoperatively, the patient showed no signs of recurrence during follow-up, with complete resolution of symptoms. The combined approach ensured thorough removal of mucus-secreting glands and cystic components, preventing recurrence. The optimal treatment for a plunging ranula involves excision of the lesion and the involved gland. Intraoperative ultrasonography aids in ensuring complete excision of all cystic components, reducing recurrence risk.